Penerapan Pendekatan Realistic Mathematics Education untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Statistika Kelas VIII-1 SMP Nurul Islam Indonesia Medan - Vivi Aledya; Sri Lestari Manurung (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine students' ability to understand mathematical concepts through the application of the Realistic Mathematics Education learning approach and to find out how the students' answers process in solving problems on tests of students' ability to understand mathematical concepts after applying the Realistic Mathematics Education learning approach in class VIII-1 of SMP Nurul Islam Indonesia Medan. This type of research is classroom action research through cyclical learning stages. The subjects of this research were 13 students in class VIII-1 of SMP Nurul Islam Indonesia Medan and the object of this research was the students' ability to understand mathematical concepts by applying the Realistic Mathematics Education learning approach to statistical material. Based on the research results, it was found that by applying the Realistic Mathematics Education learning approach, students' ability to understand mathematical concepts in statistical material in class VIII-1 at Nurul Islam Indonesia Middle School in Medan was improved, namely in cycle I the average student ability was only 30.76 with a completion percentage of only 8% of students completed. In cycle II the average student ability increased to 92.95 with a student completion percentage of 100%, so that students had met the classical completion percentage, namely ≥85%. The results of this research show that by applying the Realistic Mathematics Education learning approach to statistics material in class VIII-1 of Nurul Islam Indonesia Middle School in Medan, students can improve their ability to understand mathematical concepts.